1992
DOI: 10.1111/j.1360-0443.1992.tb02662.x
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of a change in formulation of methadone prescribed in a drug clinic

Abstract: Methadone mixture DTF (1mg in 1ml) is a safe non-injectable alternative to methadone tablets (5mg). It also allows for a more gradual detoxification from opiate dependence. For these reasons it was decided to 'rationalise' our prescribing so that methadone in mixture form only would be dispensed. At the beginning of 1989, 66 opiate-dependent patients were receiving methadone tablets, 61 the methadone mixture. We report the consequences of instituting a policy change which was clearly very unpopular with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…On the contrary, our results demonstrated a significant 11.5% increase in rates of heroin injection immediately after the policy change. These findings are in line with previous research documenting high rates of what has been defined as “change intolerance” to the introduction of new methadone formulations (Silver & Shaffer, 1996; Steels, Hamilton, & McLean, 1992). Although limited clinical evidence support a psychological (e.g., perceived lower efficacy due to lower volumes) rather than a biological or pharmacological basis underlying withdrawal symptoms (Gourevitch, et al, 1999), it may also be partially explained by dispensation challenges with the new formulation, including difficulties in titrating doses (McNeil, et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, our results demonstrated a significant 11.5% increase in rates of heroin injection immediately after the policy change. These findings are in line with previous research documenting high rates of what has been defined as “change intolerance” to the introduction of new methadone formulations (Silver & Shaffer, 1996; Steels, Hamilton, & McLean, 1992). Although limited clinical evidence support a psychological (e.g., perceived lower efficacy due to lower volumes) rather than a biological or pharmacological basis underlying withdrawal symptoms (Gourevitch, et al, 1999), it may also be partially explained by dispensation challenges with the new formulation, including difficulties in titrating doses (McNeil, et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Regardless, its adverse social and health effects cannot be overlooked. Indeed, in other settings, change intolerance has been associated with treatment disruptions, decreased social stability, relapse to illicit drug use, and involvement in illegal income-generation activities (Greer, et al, 2016; McNeil, et al, 2015; Silver & Shaffer, 1996; Steels, et al, 1992). …”
Section: Discussionmentioning
confidence: 99%
“…While this may in part be a psychological phenomenon, possibly due to the reduced medication volume dispensed with the newer formulation, dispensation challenges and pharmacological or pharmacokinetic effects might also explain these dynamics. Meanwhile, previous studies of methadone formulation changes (tablets to liquid formulations) have documented high rates of ‘change intolerance’ resulting in adverse outcomes (e.g., withdrawal symptoms, injection opiate use) (Silver & Shaffer, 1996; Steels, Hamilton, & McLean, 1992), underscoring the need for pharmacokinetic studies undertaken real world conditions. This is of particular importance as populations enrolled in MMT increasingly report polysubstance use and require a variety of daily medications to manage complex comorbidities (Sharif et al, 2013), which potentially impact treatment effectiveness (McCance-Katz, Sullivan, & Nallani, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies support our findings that medication transition periods can have pronounced bio-psychosocial impacts on patients. In the United Kingdom, change in methadone formulation in 1992 was correlated with an increase use of non-prescription opioids, decline in social stability, and an increase in pharmacy break-ins [ 20 ]. A clinical study conducted by Soyka and Zingg in 2009 found the transfer from racemic methadone to (R)-methadone decreased withdrawal symptoms, cravings, and supplementing with additional drugs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%